Pengaruh Resiprositas, Altruisme Dan Stres Kerja Terhadap Produktivitas Di Masa Pandemi Covid 19 - Firman Fauzi; Bernika Caroline (Jurnal Dinamika Ekonomi & Bisnis, 2022)
The goal of this study was to look at the effects of reciprocity, altruism (cooperation or mutual assistance), and stress on employee productivity during the Covid 19 pandemic The Covid-19 pandemic, which changed employee work patterns in the scope of government, agencies, the private sector, and others, motivated this research. Working from home, or WFH, was the employee's work pattern during the Covid 19 pandemic. So that it is clear how the Covid-19 Virus pandemic affects reciprocity between employees or employees with the company, cooperation and mutual assistance (altruism) among employees, and managing work-related stress at home. The entire population of 80 employees at the Housing Marketing Company was used as the research sample in quantitative research with saturated samples. When gathering data, the survey method with a questionnaire instrument was used. The data analysis method employs a causal quantitative approach with the SPSS version 25 software. According to this study, reciprocity has a positive and significant effect on productivity during the Covid 19 period, while Altruism has a positive but insignificant effect and Work Stress has a negative and insignificant effect on productivity during the Covid 19 period.